The Ontology of Logic: A Philosophical Inquiry into the Nature of Reasoning - Mehdi, Muhammad Ansar; Maqsood, Dr. Sidra (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
This article aims to explore the ontological status of logic while tracing its journey from Classical Greek philosophy to the works of renowned contemporary thinkers. Classical thinkers explored the definite nature of logic in either Plato’s transcendent world of Ideas or Aristotle’s Universal Forms in matter. In the Enlightenment period, Emmanuel Kant positioned logic within the formal structure of thought, while Frege and Russell, two prominent contemporary philosophers, advocated for the objective existence of logic. In contrast, Quine and Wittgenstein questioned the traditional metaphysical grounding of logic and reconsidered logic as linguistically constructed and empirically revisable. The paper proposes Synthesis through phenomenological perspectives, particularly Heidegger’s notion of being-in-the-world and thrownness (Geworfenheit), to reveal how logic is encountered within the human condition. This approach allows for the synthesis of divergent views, aiming to provide a coherent and rational account of logic’s ontological status. From the primary texts, secondary scholarship, and credible tertiary sources, this study explores the ontological status of logic and establishes the influence of logic on epistemology, mathematics, and artificial intelligence. Drawing on the understanding of logic by realists as the method of organizing rational inquiry, conventionalists as a social construct, and my phenomenological resolution as a continued lived experience, the paper argues that various understandings in explaining the role of logic are crucial in structuring the course of rational inquiry across the disciplines.